Integration of GWAS and transcriptome analysis to identify temperature-dependent genes involved in germination of rapeseed (Brassica napus L.) - Wang, Ruisen; Wu, Guangyu; Zhang, Jingyi; Hu, Weizhen; Yao, Xiangtan; Jiang, Lixi; Zhu, Yang (Frontiers in Plant Science, 2025)
Low temperature germination (LTG) is one of crucial agronomic traits for field-grown rapeseed in the Yangtze River Basin, where delayed sowing frequently exposes germination to cold stress. Because of its importance, the genetic basis underlying rapeseed germination under different temperatures has been continuously focused. By long-term field observation, we screened out two cultivars with significantly different LTG performance (JY1621 and JY1605) in field and lab conditions, which therefore were further used for the transcriptome sequencings at three key timepoints under normal and low temperatures. Comparative analysis among multiple groups of differentially expressed genes (DEGs) revealed a set of either early or late temperature response germination (ETRG or LTRG) genes, as well as cold-tolerant (CDT) and temperature-insensitive (TPI) candidate regulators at different germination stages. Furthermore, we performed a genome-wide association study (GWAS) using germination index of 273 rapeseed accessions and identified 24 significant loci associated with germination potential under normal temperatures. Through integrated analysis of transcriptome sequencing and GWAS, we identified a series of candidate genes involved in temperature-dependent germination. Based on the comprehensive analysis, we hypothesized that BnaA3.CYP77A4 and BnaA3.NAC078 could be important candidate genes for LTG due to their expression patterns and haplotype distributions. This study performed the multi-omics analysis on temperature-dependent germination and provided potential genetic loci and candidate genes required for robust germination, which could be further considered for low-temperature germination breeding of rapeseed.